EFEKTIVITAS PELAKSANAAN PROGRAM PEMBANGUNAN PEDESAAN DI DESA KAUNERAN 1 KECAMATAN SONDER - OLBATA, APRILIA; RURU, JOORIE MARHAEN; PALAR, NOVIE ANDERS (Sam Ratulangi University, 2018)
The implementation of the Rural Development Program is one form of the government indeveloping villages. With rural development, it is expected that a change will occur in various aspects,including efforts to improve the welfare of the community through the pace of economic growth. Thepurpose of this study is to determine the level of effectiveness and the factors that influence it. To measurethe level of effectiveness, researchers use three measures of effectiveness according to Ducan, who isquoted by Richard M. Steers in his book